Factors controlling instability of homogeneous soil slopes under rainfall - R.B., Rezaur; H., Rahardjo; T.H., Ong; E.C., Leong (2007)

(untitled)
Rainfall-induced slope failure is a common geotechnical problem in the tropics where residual soils are abundant. Although the significance of rainwater infiltration in causing landslides is widely recognized, there have been different conclusions as to the relative roles of antecedent rainfall to landslides. The relative importance of soil properties, rainfall intensity, initial water table location and slope geometry in inducing instability of a homogenous soil slope under different rainfall was investigated through a series of parametric studies. Soil properties and rainfall intensity were found to be the primary factors controlling the instability of slopes due to rainfall, while the initial water table location and slope geometry only played a secondary role. The results from the parametric studies also indicated that for a given rainfall duration, there was a threshold rainfall intensity which would produce the global minimum factor of safety. Attempts have also been made to relate the findings from this study to those observed in the field by other researchers. Results of this parametric study clearly indicated that the significance of antecedent rainfall depends on soil permeability. Â© 2007 ASCE.